NiAlGa catalyst, preparation method thereof and application of NiAlGa catalyst in catalysis of ammonia decomposition

Through the gallium-doped nickel-aluminum hydrotalcite catalyst Ni3Al1-xGax, the problem of insufficient activity of ammonia decomposition catalysts in the prior art is solved, and efficient and stable ammonia decomposition hydrogen production reaction is achieved, which reduces energy consumption and cost and significantly improves the Catalytic activity and conversion rate.

CN119114099APending Publication Date: 2024-12-13ZHENGZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411260890.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art has shortcomings in the development and mechanism of ammonia decomposition catalysts, especially in terms of improving ammonia decomposition reaction activity and reducing energy consumption and costs.

Method used

Ni3Al1-xGax, a gallium-doped nickel-aluminum hydrotalcite catalyst, was prepared by hydrothermal method and reduction method, with a uniformly dispersed sheet structure and improved acidic sites, and was used for ammonia decomposition and catalyzed hydrogen production reaction.

Benefits of technology

It significantly improves the catalytic activity and stability of the hydrogen production reaction of ammonia decomposition, reduces energy consumption and cost, and maintains high-efficiency activity under high temperature conditions, with an ammonia decomposition conversion rate reaching 99.5%, and a hydrogen production rate reaching 26.6 mmol·gcat-1· h-1, activation energy is 37.7 kJ/mol.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114099A_ABST
    Figure CN119114099A_ABST
Patent Text Reader

Abstract

The invention discloses a gallium-doped nickel-aluminum hydrotalcite catalyst, which is a Ni3Al1-xGax catalyst, in which 0 lt, 0 lt, 0 lt, 0 lt, 0 lt, 0 lt, 0 lt, 0 lt and 0 lt; xlt; and 0.1. The preparation method of the catalyst comprises the following steps: adding nickel nitrate, aluminum nitrate, gallium nitrate and urea into deionized water to obtain a blue suspension; carrying out a hydrothermal reaction to obtain a blue precipitate; washing and collecting the precipitate, and drying in a drying oven to obtain a blue solid; then calcining to obtain light gray powder; and subsequently putting into a hydrogen tube furnace for reduction to obtain the final catalyst. The catalyst has a high specific surface area and has a mixed metal oxide and a metal state. Ni < 2 + >, Al < 3 + > and Ga < 3 + > form a positive charge layer in densely arranged OH <-> octahedral holes in the hydrotalcite precursor, the positive charge layer is converted into a mixed metal oxide after calcination, and metal Ni and other oxides are further formed after hydrogen reduction. The gallium-doped catalyst shows high activity and high stability in ammonia decomposition hydrogen production reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysis, and in particular relates to a NiAlGa catalyst and a preparation method thereof, and an application of catalytic ammonia decomposition. Background Art

[0002] As a representative of clean energy, hydrogen plays a vital role in the global energy transition. Hydrogen has the characteristics of high energy density and zero emissions, and is widely regarded as the core of the future energy system. However, although traditional hydrogen production methods such as steam reforming, partial oxidation, and water electrolysis have been industrialized, they still face challenges such as high energy consumption, high cost, and high infrastructure requirements. In contrast, ammonia (NH3) has a high energy density and is an effective hydrogen carrier that is liquid under ambient conditions, providing a feasible hydrogen storage medium. However, the development of efficient ammonia decomposition catalysts and their mechanisms remain unclear.

[0003] In recent years, catalysts with high surface area supports (such as CaNH, Al2O3 and SiO2) and electron-donating promoters (such as Ce, La, Na and K) have been widely studied to enhance the activity of ammonia decomposition. Many transition metals (such as Ni) show good catalytic activity for NH3 decomposition at relatively low temperatures and have become a recent research hotspot due to their low cost of large-scale operation. Among them, hydrotalcite structures have a unique layered structure and tunable chemical composition, showing superior catalytic performance. Divalent and trivalent cations are accommodated in tightly packed OH-configured octahedral pores to form positively charged brucite-like layers, with anions and water molecules located between these layers to balance the positive charge. The tunable metal species and their relative proportions vary greatly. After calcination, these hydrotalcites are converted into uniform metal oxides with the characteristics of large specific surface area, small grains, good thermal stability and tunable pH. Literature shows that in the water gas reaction, Cu-Mg-Al hydrotalcite-based catalysts have a unique interlayer structure that is conducive to the reduction of Cu species at lower temperatures to generate highly active CuO and Cu2O species. In addition, the designed hydrotalcite-based catalysts, when combined with CO2 adsorbents, can effectively prevent the oxidation of active sites and ensure the production of high-purity hydrogen. This significantly enhances the catalytic activity in the water gas shift reaction and is suitable for adsorption enhancement processes. There are also literatures showing that the catalyst made of Cu-ZnO-Al2O3 mixed with different amounts of hydrotalcite (named CZA-HT) exhibits good adsorption capacity for reactant gases, significantly increases the CO2 concentration around the active sites, and thus promotes the reaction. However, little is known about the promoting effect of hydrotalcite-based catalysts on ammonia decomposition reactions. Summary of the invention

[0004] In view of the shortcomings of the existing methods, the present invention provides a gallium-doped nickel-aluminum hydrotalcite catalyst and a preparation method and application thereof.

[0005] In a first aspect, the present invention provides a gallium-doped nickel-aluminum hydrotalcite catalyst, which is Ni3Al 1-x Ga x catalyst, wherein 0 < x < 0.1.

[0006] Preferably, in the Ni3Al 1-x Ga x catalyst, 0 < x ≤ 0.05, more preferably 0 < x ≤ 0.01.

[0007] Preferably, the surface area of the Ni3Al 1-x Ga x catalyst is 75 - 126 m 2 / g.

[0008] In a second aspect, the present invention provides a method for preparing the Ni3Al 1-x Ga x catalyst, comprising the following steps: S1. Add nickel nitrate, aluminum nitrate, gallium nitrate and urea to deionized water, and stir to obtain a blue suspension; S2. Transfer the blue suspension to a hydrothermal autoclave, carry out a hydrothermal reaction to form a blue precipitate; S3. Wash the blue precipitate with deionized water, filter by suction, and dry to obtain a blue solid; S4. Calcinate the blue solid in a muffle furnace to obtain a light gray powder; S5. Reduce the light gray powder in a hydrogen tube furnace to obtain the Ni3Al 1-x Ga x catalyst.

[0009] Preferably, in step S1, the amounts of nickel nitrate, aluminum nitrate, gallium nitrate, and urea are 4.34 - 4.36 g, 1.87 - 1.89 g, 61 - 63 mg, and 3.5 g - 3.7 g respectively, preferably 4.35 g of nickel nitrate, 1.881 g of aluminum nitrate, 20.9 mg of gallium nitrate, and 3.6 g of urea, to ensure that in the final product Ni3Al 1-x Ga x catalyst, 0 < x < 0.1.

[0010] Preferably, in step S2, the temperature of the hydrothermal reaction is 120 - 150 °C and the time is 8 - 10 h.

[0011] Preferably, in step S3, the drying temperature is 100 - 130 °C and the time is 10 - 15 h.

[0012] Preferably, in step S4, the calcination temperature is 450-550° C., and the holding time is 2-6 h.

[0013] Preferably, in step S5, the reduction temperature is 450-550° C., and the insulation time is 10-30 min.

[0014] Preferably, in steps S4 and S5, the heating rate of the calcination is 1-3°C / min to ensure that the particles maintain small grains during the metal reduction process.

[0015] In a third aspect, the present invention provides the Ni3Al 1-x Ga x Application of catalyst in the catalytic decomposition of ammonia to produce hydrogen.

[0016] Preferably, the temperature of the ammonia decomposition catalytic hydrogen production reaction is 300-800° C. and the time is 8-16 h.

[0017] The positive beneficial effects of the present invention are: 1. The catalyst of the present invention is a gallium-doped nickel-aluminum hydrotalcite catalyst having a uniformly dispersed lamellar structure. At the same time, the gallium doping increases the acid sites on the catalyst surface and improves the adsorption and dissociation efficiency of ammonia molecules. 0.99 Ga 0.01 (Example 1), Ni3Al 0.97 Ga 0.03 (Example 2), Ni3Al 0.95 Ga 0.05 (Example 3), Ni3Al 0.90 Ga 0.10 The surface areas of the catalysts of Example 4, Ni3Al (Comparative Example 1) and Ni3Ga (Comparative Example 2) are 125.7 m 2 / g, 123.4 m 2 / g, 110.3 m 2 / g, 76.2 m 2 / g, 122.7 m 2 / g, 15.6 m 2 / g, among which Ni3Al 0.99 Ga 0.01 (Example 1) The surface area of ​​the catalyst is the highest among the series of catalysts. 1-x Ga x Based on the high surface area and small grain size, the catalyst significantly improves the catalytic activity of ammonia decomposition to produce hydrogen through gallium doping.

[0018] 2. The application of the catalyst of the present invention in the ammonia decomposition hydrogen production reaction shows excellent catalytic performance.1-x Ga x The catalyst can still maintain stable activity after stage heating and cooling (stability test of ammonia decomposition hydrogen production process), the reaction conditions are mild and efficient, Ni3Al 0.99 Ga 0.01 (Example 1) The catalytic activity of the catalyst at 500°C is 86.8%, which is significantly higher than the catalytic activity of pure Ni3Ga (Comparative Example 2) and Ni3Al (Comparative Example 1). Correspondingly, the hydrogen production rate reaches 26.6mmol·gcat -1 ·h -1 , the activation energy is 37.7 kJ / mol. At 450℃, 500℃ and 550℃, Ni3Al 0.99 Ga 0.01 (Example 1) The catalyst exhibited the highest ammonia decomposition activity, with a conversion rate of 99.5% at 550°C, almost achieving complete conversion. This high-performance catalyst can significantly reduce the energy consumption and cost of hydrogen production by ammonia decomposition, promote the widespread application of hydrogen energy, and contribute to the sustainable development of clean energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The Ni3Al 1-x Ga x Catalyst preparation flow chart; Figure 2 For the preparation of Ni3Al 0.99 Ga 0.01 (Example 1), Ni3Al 0.97 Ga 0.03 (Example 2), Ni3Al 0.95 Ga 0.05 (Example 3), Ni3Al 0.90 Ga 0.10 (Example 4), Ni3Al (Comparative Example 1) and Ni3Ga (Comparative Example 2) catalysts; Figure 3 For the preparation of Ni3Al 0.99 Ga 0.01 SEM image, TEM image and EDS mapping image of (Example 1); Figure 4 For the preparation of Ni3Al 0.99 Ga 0.01 (Example 1), Ni3Al 0.97 Ga 0.03 (Example 2), Ni3Al 0.95 Ga 0.05 (Example 3), Ni3Al 0.90 Ga0.10 NH3-tpd diagrams of (Example 4), Ni3Al (Comparative Example 1) and Ni3Ga (Comparative Example 2) catalysts; Figure 5 For the preparation of Ni3Al 0.99 Ga 0.01 (Example 1), Ni3Al 0.97 Ga 0.03 (Example 2), Ni3Al 0.95 Ga 0.05 (Example 3), Ni3Al 0.90 Ga 0.10 (Example 4), Ni3Al (Comparative Example 1) and Ni3Ga (Comparative Example 2) Ammonia decomposition rate and hydrogen generation rate.

[0021] Specific embodiment In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0022] Example 1 A Ni3Al 1-x Ga x The preparation method of the catalyst (x=0.01) is as follows: Figure 1 As shown, the following steps are included: S1. Add 4.35 g nickel nitrate, 1.881 g aluminum nitrate, 20.9 mg gallium nitrate and 3.6 g urea to 50 mL deionized water and stir to obtain a blue suspension; S2, the blue suspension was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and subjected to hydrothermal reaction in an oven at 140 °C for 9 h to obtain a blue precipitate; S3, washing the blue precipitate with 2 L of deionized water, filtering, and drying the precipitate at 110 °C for 12 h to obtain a blue solid; S4, placing the blue solid in a muffle furnace, and calcining at 500 °C for 4 h at a heating rate of 1 °C / min to obtain a light grey powder; S5. The light grey powder was placed in a hydrogen tubular furnace and calcined at 500 °C for 2 h at a heating rate of 1 °C / min to obtain Ni3Al 0.99 Ga 0.01 catalyst.

[0023] Example 2 This embodiment is basically the same as embodiment 1, except that: the amount of reactants added in step S1 is: 4.35g nickel nitrate, 1.843g aluminum nitrate, 62.7mg gallium nitrate and 3.6g urea, and the obtained product is Ni3Al 0.97 Ga0.03 catalyst.

[0024] Example 3 This embodiment is basically the same as embodiment 1, except that: the amount of reactants added in step S1 is: 4.35g nickel nitrate, 1.805g aluminum nitrate, 104.5mg gallium nitrate and 3.6g urea, and the obtained product is Ni3Al 0.95 Ga 0.05 catalyst.

[0025] Example 4 This embodiment is basically the same as embodiment 1, except that: the amount of reactants added in step S1 is: 4.35g nickel nitrate, 1.9g aluminum nitrate, 209mg gallium nitrate and 3.6g urea, and the obtained product is Ni3Al 0.90 Ga 0.10 catalyst.

[0026] Comparative Example 1 This embodiment is basically the same as embodiment 1, except that: the addition amount of the reactants in step S1 is: 4.35 g nickel nitrate, 1.9 g aluminum nitrate and 3.6 g urea, and the obtained product is Ni3Al catalyst.

[0027] Comparative Example 2 This embodiment is basically the same as embodiment 1, except that: in step S1, the added amounts of reactants are: 4.35 g nickel nitrate, 2.09 g gallium nitrate and 3.6 g urea, and the obtained product is a Ni3Ga catalyst.

[0028] Catalyst structure characterization Ni3Al prepared by the present invention 0.99 Ga 0.01 (Example 1), Ni3Al 0.97 Ga 0.03 (Example 2), Ni3Al 0.95 Ga 0.05 (Example 3), Ni3Al 0.90 Ga 0.10 The surface areas of the catalysts of Example 4, Ni3Al (Comparative Example 1) and Ni3Ga (Comparative Example 2) are 125.7 m 2 / g, 123.4 m 2 / g, 110.3 m 2 / g, 76.2 m 2 / g, 122.7 m 2 / g, 15.6 m 2 / g, among which Ni3Al 0.99 Ga 0.01The surface area of ​​the catalyst (Example 1) is the highest among the catalysts in the series.

[0029] Figure 2 For the preparation of Ni3Al 0.99 Ga 0.01 (Example 1), Ni3Al 0.97 Ga 0.03 (Example 2), Ni3Al 0.95 Ga 0.05 (Example 3), Ni3Al 0.90 Ga 0.10 (Example 4), Ni3Al (Comparative Example 1) and Ni3Ga (Comparative Example 2) catalysts. Figure 2 It can be seen that after hydrogen reduction of the catalyst, Ni (111), (200) and (220) crystal planes can be detected, no gallium diffraction peaks are detected, and the peak intensity increases with the increase of gallium content in Ni and NiO, which may be due to gallium entering the crystal lattice.

[0030] Figure 3 For the preparation of Ni3Al 0.99 Ga 0.01 (Example 1) SEM, TEM and EDS mapping. Figure 3 It can be seen that Ni3Al 0.99 Ga 0.01 The sample has a distinct flaky structure, consistent with the morphology of layered double hydroxide, with particle sizes ranging from tens of nanometers to hundreds of nanometers. The lattice spacing of 0.199 nm and 0.204 nm correspond to the NiO (200) and Ni (111) planes, respectively. HRTEM images and EDS elemental images show that Ni, Al and Ga are uniformly dispersed. Ni 2+ 、Al 3+ And Ga 3+ A positively charged layer is formed in the closely packed OH-octahedral pores in the hydrotalcite precursor, which is converted into mixed metal oxides after calcination and further forms metallic Ni and other oxides after hydrogen reduction.

[0031] Catalyst performance test The prepared catalyst Ni3Al 0.99 Ga 0.01 (Example 1), Ni3Al 0.97 Ga 0.03 (Example 2), Ni3Al 0.95 Ga 0.05 (Example 3), Ni3Al 0.90 Ga 0.10(Example 4), Ni3Al (Comparative Example 1) and Ni3Ga (Comparative Example 2) were used for ammonia decomposition reaction. 50 mg of catalyst was placed in the center of the constant temperature zone of the reaction tube. The diameter of the reaction tube was 8 mm and the bed height was 30 mm. Before the reaction, the catalyst was pretreated with a 25% H2 / Ar gas flow at 500°C for 2 h. Subsequently, the gas was converted into an NH3 flow. All activity tests were carried out at atmospheric pressure in the temperature range of 350-700°C. The outlet components were analyzed using an online gas chromatograph (GC2060) equipped with a TCD detector and a dedicated 5A packed ammonia gas chromatographic column.

[0032] X NH3 = ([NH3] in -[NH3] out ) / [NH3] in × 100% r H2 = V NH3 22.4 X NH3 1.5 m cat. Among them, [NH3] in , [NH3] out , V NH3 , and cat., are feed stream NH3 concentration, outlet stream NH3 concentration, NH3 flow rate and catalyst mass, respectively.

[0033] Figure 4 For the preparation of Ni3Al 0.99 Ga 0.01 (Example 1), Ni3Al 0.97 Ga 0.03 (Example 2), Ni3Al 0.95 Ga 0.05 (Example 3), Ni3Al 0.90 Ga 0.10 NH3-tpd diagram of (Example 4), Ni3Al (Comparative Example 1) and Ni3Ga (Comparative Example 2) catalysts. Figure 4 It can be seen that the desorption of ammonia occurs in the temperature range of 50-420℃. The position of the desorption peak indicates that the introduction of Ga affects the acid sites. Samples without Ga or with high Ga content, such as Ni3Ga (Comparative Example 2) and Ni3Al 0.90 Ga 0.10 (Example 4), there is almost no desorption peak, indicating that the acid sites are lacking or insufficient. As the Ga content decreases (from Ni3Al 0.90 Ga 0.10 (Example 4) to Ni3Al 0.99 Ga 0.01(Example 1)), the ammonia desorption peak is more obvious, and the main desorption peak appears between 200 and 300 ° C, showing a medium acid site intensity. This shows that a small amount of Ga doping increases the number and intensity of acid sites on the catalyst surface. Gallium doping may also affect the formation of hydrogen bonds and the dissociation of hydrogen atoms. Areas with high electron density are more likely to attract hydrogen atoms and promote the generation of hydrogen.

[0034] Figure 5 For the preparation of Ni3Al 0.99 Ga 0.01 (Example 1), Ni3Al 0.97 Ga 0.03 (Example 2), Ni3Al 0.95 Ga 0.05 (Example 3), Ni3Al 0.90 Ga 0.10 (Example 4), Ni3Al (Comparative Example 1) and Ni3Ga (Comparative Example 2) 0.99 Ga 0.01 The catalyst has good catalytic activity. -1 ·h -1 When the temperature is 550℃, almost complete conversion is achieved. Figure 5 As shown in a, Ni3Al 0.99 Ga 0.01 (Example 1) The catalytic activity at 500°C is 86.8%, which is significantly higher than the catalytic activity of pure Ni3Ga (Comparative Example 2) and Ni3Al (Comparative Example 1). Correspondingly, the hydrogen production rate reaches 26.6 mmol·gcat -1 ·h -1 , the activation energy is 37.7 kJ / mol. At 450℃, 500℃ and 550℃, Ni3Al 0.99 Ga 0.01 The catalyst (Example 1) showed the highest ammonia decomposition activity, with a conversion rate of 99.5% at 550°C. As the Ga doping level increased, the ammonia decomposition activity first increased and then decreased, with Ni3Ga (Comparative Example 2) having the lowest decomposition activity. This result shows that a small amount of gallium doping helps to improve the catalyst activity, but excessive gallium doping may reduce the number of active sites or cause adverse changes in the surface structure.

[0035] The stability test of the ammonia decomposition hydrogen production process was conducted by first operating at 500°C for 50 hours, then heating up to 550°C for 50 hours, and then cooling down to 500°C for 50 hours. 0.99 Ga 0.01 (Example 1), Ni3Al0.97 Ga 0.03 (Example 2), Ni3Al 0.95 Ga 0.05 (Example 3), Ni3Al 0.90 Ga 0.10 (Example 4) remained stable during testing.

[0036] With the above-mentioned ideal embodiment of the present invention as inspiration, through the above-mentioned description, relevant staff can make various changes and modifications without departing from the technical idea of ​​the present invention. The technical scope of the present invention is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims. Any equivalent changes or modifications made according to the spirit of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A gallium-doped nickel-aluminum hydrotalcite catalyst, which is Ni3Al 1-x Ga x Catalyst, wherein 0<x<0.1。 2. The catalyst according to claim 1, wherein The Ni3Al 1-x Ga x In the catalyst, 0 <x≤0.05。 3. The catalyst according to claim 1, wherein The Ni3Al 1-x Ga x The surface area of ​​the catalyst is 75-126 m 2 / g.

4. The method for preparing the catalyst according to any one of claims 1 to 3, comprising the steps of: S1. Add nickel nitrate, aluminum nitrate, gallium nitrate and urea into deionized water and stir to obtain a blue suspension; S2, transferring the blue suspension to a hydrothermal reactor for hydrothermal reaction to generate a blue precipitate; S3, washing the blue precipitate with deionized water, filtering, and drying to obtain a blue solid; S4, placing the blue solid in a muffle furnace and calcining it to obtain a light grey powder; S5, placing the light grey powder into a hydrogen tubular furnace for reduction to obtain the Ni3Al 1-x Ga x catalyst.

5. The method according to claim 4, wherein: In step S1, the amounts of nickel nitrate, aluminum nitrate, gallium nitrate and urea are 4.34-4.36 g, 1.87-1.89 g, 61-63 mg and 3.5 g-3.7 g, respectively.

6. The method according to claim 4, wherein: Preferably, in step S2, the temperature of the hydrothermal reaction is 120-150° C., and the time is 8-10 h.

7. The method according to claim 4, wherein: In step S3, the drying temperature is 100-130° C. and the drying time is 10-15 h.

8. The method according to claim 4, wherein: In step S4, the calcination temperature is 450-550° C., and the holding time is 2-6 h.

9. The method according to claim 4, wherein: In step S5, the reduction temperature is 450-550° C., and the insulation time is 10-30 min.

10. Use of the catalyst according to any one of claims 1 to 3 in the catalytic production of hydrogen by decomposition of ammonia.

Citation Information

Patent Citations

  • Hydrogen generation catalyst and method for producing hydrogen

    CN104640628A

  • Nickel-gallium alloy catalyst as well as preparation method and application thereof

    CN112705208A

  • Precious metal methanol-to-hydrogen catalyst as well as preparation method and application thereof

    CN114534722A

  • Ni / LaAlOx composite catalyst, preparation method thereof and application of Ni / LaAlOx composite catalyst in hydrogen production through thermocatalytic ammonia decomposition

    CN118204089A

  • Method for obtaining high alcohols

    US20150148569A1